Dietetic Supplements for Weight Reduction: Medical and Ethical Dilemmas [Suplementos Dietéticos Para Reducir de Peso: Dilemas Médicos y Éticos] - Vanegas-Lopez, J (Sociedad Medica de Santiago, 2014)
Obesity is an important public health problem. Dietetic supplements are commonly used by obese patients who are not aware of the effectiveness or potential harms of these products. The aim of this paper is to discuss the ethical dilemma associated with the use of these supplements. The principles of autonomy, beneficence and justice are involved. Obesity as a chronic disease, requires qualified medical care. Obese individuals should be aware of their disease and voluntarily agree to receive professional care. © 2014, Sociedad Medica de Santiago. All rights reserved.